Determinants of Chinese demand for tourism in Malaysia - Puah, Chin Hong; Huan, Suk Hie; Thien, Fung Thai (Prague Development Center,Prague Development Center s.r.o., 2018)
Tourism sector in Malaysia has always been one of its focal service industries not only in the past, but in the future as well in which Malaysian government has been focusing on diverting its economic activities from a resource-based to a service-based economy in its new economic model. China, a strongly emerging economy has been ranked as the third main tourist generating country for Malaysia since 2012. Hence, this study empirically identifies the macroeconomic determinants affecting the tourism demand from China to Malaysia. These determinants include real income, travel cost, exchange rate and trade openness. Particularly, real income and trade openness are evident to positively affect Chinese tourism demand while travel cost and exchange rate are found to adversely influence Chinese tourists’ decision to travel to Malaysia.